THE YOGIC EXPERIENCE UNDER SCIENTIFIC RESEARCH: . - Vithayathil, Thomas (Journal of Dharma, 1979)
Time and again man and the mystery of his being has been the focal POInt. of our st~?y and research. "Humanity's attention", says Dr. AlexIs Carrel, must turn from the machines and the wOrld. of inanimate matter, to the body and soul of man, to the organl~ and mental processes which have created the machines and the unIverse of Newton ~n~ Einstein."1 Over the years,' man has devoted a great deal of hIS time and energy to the study of mental phenomena, the macrocosm; he has practicaUy ignored the sublime and nobl~ demands of the innerself, the microcosm. Psychologists regard. thIs ~eglected source of energy as the untapped human potentIal. It